Detection of Specific Autoantibodies in Sera with Negative Antinuclear Antibody by Indirect Immunofluorescence Assay but Positive by Enzyme Immunoassay - Ronnachai Viriyataveekul; Jaruda Kobkitjaroen (Siriraj Medical Journal, 2019)
Objective: The aim of this study was to investigate the predictive value of positive enzyme immunoassay (EIA) for detection of specific autoantibodies in sera negative for antinuclear antibody (ANA) by indirect immunofluorescence (IIF) assay, but positive for ANA by EIA. Methods: Eighty sera that tested negative for ANA by IIF, but positive for ANA by EIA were included. All sera were tested for specific autoantibodies by line immunoassay (LIA). The positive predictive value (PPV) of EIA was calculated using LIA result as a reference standard. Medical records of patients were reviewed. Clinical findings at the time of blood sampling for ANA testing and at 5 years after sampling were obtained. Results: Twenty-eight sera (35%) were found to be positive by LIA. The PPV of EIA for detection of specific autoantibodies at the manufacturer’s recommended cut-off was 35.0% (95% CI: 24.5-45.5%). The most prevalent antibodies were anti-SSA/Ro60 (64.3%, 95% CI: 46.5-82.0%), anti-Ro52 (25.0%, 95% CI: 9.0-41.0%), and anti-SSB/ La (10.7%, 95% CI: 0-22.2%). A diagnosis of systemic autoimmune rheumatic disease was established in 7 patients (25%) at the time of blood sampling, and 4 patients (14.3%) were diagnosed with non-rheumatic autoimmune disease. Conclusion: EIA testing in IIF-ANA negative sera yielded a chance to detect antinuclear antibodies. However, the poor PPV of EIA may have low benefit in real-life clinical practice. Anti-SSA/Ro60 was the most prevalent antibody detected. A high proportion of LIA-ANA positive patients were not diagnosed as autoimmune disease at the time of antibody detection.